Towards the identification of effective supervisory practices in Catholic secondary schools in Metro Manila - Santos, Celedonia San Luis (Animo Repository, 1990)
This research assesses the effectivity of the supervising tasks and styles in Catholic secondary schools in Metro Manila and identifies measures of supervisory effectiveness. The descriptive-comparative method of research was employed to describe, analyze and compare the perceptions of principals, academic coordinators, and faculty concerning the supervisory tasks and styles of academic coordinators of 94 Catholic secondary schools in Metro Manila. The study was also correlational in nature because it attempted to determine the significant correlates of the academic coordinators' extent of performance of their supervisory tasks and the level of desirability of their predominant supervisory styles. The study involved 1,949 classroom teachers, 396 academic coordinators and 94 principals of 94 Catholic secondary schools in Metro Manila during the SY 1989-1990. Survey questionnaires developed by the researcher were used as primary data-gathering instruments. Descriptive statistics such as means, standard deviations, one way analysis of variance, multiple correlation and regression through stepwise regression were used in the analysis of quantitative data.The findings of the study support the following conclusions: 1. Extent of performance of the supervisory tasks of the academic coordinators tend to vary with the number of subject areas being coordinated, such that the less the number of these areas are, the more the academic coordinators are able to do their supervisory tasks. 2. Older supervisors tend to perform their supervisory tasks to a greater extent than the younger ones and are more consistent in their choice of supervisory styles. 3. The longer the length of teaching experience and the more administrative positions they have held in the past, the more desirable their supervisory styles are perceived to be. 4. The human relations supervisor who predominantly uses the motivating and the supporting styles and who is greatly concerned with curriculum improvement tend to be more highly regarded and accepted in Catholic secondary schools in Metro Manila. 5. Since the study showed that schools with higher levels of NCEE performance and accreditation had academic coordinators whose supervisory tasks were perceived to be desirable, and that consistency of use of predominant supervisory styles is positively and significantly related with the schools' level of accreditation, it may be concluded, subject to further verification, that desirability and consistency of use of supervisory styles are probable partial indicators of supervisory effectiveness.